Marital satisfaction among Husbands of Kawruh Jiwa Suryomentaram Believer Adherent - Aji, Kukuh Septio; Kristiana, Ika Febrian; Dewi, Endah Kumala (Universitas Muhammadiyah Surakarta, 2023)
Abstract. Marital satisfaction is an important part of a family's dynamic. Bearing in mind that in fact there are still many married couples who are unable to handle their marital problems properly, thus leading to divorce. Marital satisfaction is constructed in different ways, including for those who claim to adherents of the Kawruh Jiwa. This study reveals marital satisfaction in husbands who believe to the Kawruh Jiwa by using qualitative methods and a case study approach. Data collection was carried out by in-depth interviews and was guided by a semi-structured interview guide. 3 participants were selected based on a purposive sampling technique, with the following criteria: 1) male, 2) Kawruh Jiwa adherents, 3) married, 4) more than 5 years of marriage. The research was carried out at the Kawruh Jiwa spiritual center located in Gombang Village, Pabelan District, Semarang Regency. Data analysis using case study analysis. The results of this study indicate that marital satisfaction for kawruh jiwa adherents can be described through 5 interrelated themes, including 1) the meaning of marriage as a basic necessity of life, 2) the purpose of marriage as an effort to preserve offspring and preserve life, 3) kawruh laki rabi as a frame of mind in making decisions, 4) marital dynamics which include conflict resolution and cooperation, and 5) family harmonization. These findings can be used as the basis for promotive programs to increase marital satisfaction for husbands.Keywords: Husband; kawruh jiwa; marital satisfaction.